Amarjeet K. answered • 02/07/14

Tutor

4.6
(8)
Professional Engineer for Math and Science Turoring

If -6x -2 = 0 , f(x) is undefined

i.e. at x = -1/3, f9x) will be undefined - first asymptode

Similarly if 3x-6 =0 , f(x) will be undefined

i.e at x = 2, f(x) will be undefined - second asymptode

Two asymptodes = -1/3, 2

X intercept when y or f(x) is zero

f(x) = 0 when either (6x-6) =0 or (x+3)=0 i.e. x=1 and x= -3 are x intercepts

Y intercept when x = 0

f(x) = y = (0-6)(0+3)/(0-2)(0-6) = -18/12 = - 1.5

y= -1/5 is y intercept

:)